The Carbon Stocks Estimation on Tangga Community Forests of Lombok Utara - Fatwa, Abdillah; Tri Lestari, Andi; Chairil Ichsan, Andi (Jurnal Biologi Tropis, 2024)
Forests are one of the largest carbon dioxide absorbers, the forest's function as a carbon dioxide absorber causes an increase in greenhouse gases in the atmosphere, and carbon dioxide is stored in forest biomass. Forest development to increase carbon dioxide absorption can be carried out in state forest areas or private forests, which also include community forests. This research aims to estimate carbon stocks in the Tangga community forest (HKm) , in the Tangga HKm, Lombok utara, NTB. This research uses quantitative methods. The data collected is standing vegetation data. Standing vegetation data includes saplings, poles and trees by measuring diameter and height using purposive sampling collection techniques. Carbon stocks are estimated using the allometric equation formula. The total carbon reserves in the HKm Tangga obtained from each stand were 9.972,11 ton/ha. The highest carbon stock value is at the tree level with a value of 8.785,08 tons/ha, followed by the sapling level at 731,34 ton/ha, and the pole level at 455,69 tons/ha with the highest amount at the candlenut tree level (Aleurites moluccana) at 2.200,63 ton/ha and the lowest was the breadfruit (Artocarpus altilis) with a value of 1,96 ton/ha.